Frequency, Origins, and Evolutionary Role of Chromosomal Inversions in Plants - Huang, Kaichi; Rieseberg, Loren H. (Frontiers in Plant Science, 2020)
Chromosomal inversions have the potential to play an important role in evolution by reducing recombination between favorable combinations of alleles. Until recently, however, most evidence for their likely importance derived from dipteran flies, whose giant larval salivary chromosomes aided early cytogenetic studies. The widespread application of new genomic technologies has revealed that inversions are ubiquitous across much of the plant and animal kingdoms. Here we review the rapidly accumulating literature on inversions in the plant kingdom and discuss what we have learned about their establishment and likely evolutionary role. We show that inversions are prevalent across a wide range of plant groups. We find that inversions are often associated with locally favored traits, as well as with traits that contribute to assortative mating, suggesting that they may be key to adaptation and speciation in the face of gene flow. We also discuss the role of inversions in sex chromosome formation, and explore possible parallels with inversion establishment on autosomes. The identification of inversion origins, as well as the causal variants within them, will advance our understanding of chromosomal evolution in plants.